Best practices for teaching introduction to psychology - Dunn, Dana; Chew, Stephen L. (L. Erlbaum Associates, 2006)
Introductory Psychology is typically the first course new professors and graduate students teach, and with little to no teacher training. This book provides a single resource for both novice and veteran teachers to improve their effectiveness in teaching this challenging course.